Glucocorticoids improve endothelial function in rheumatoid arthritis: a study in rats with adjuvant-induced arthritis. (9th March 2017) - Verhoeven, F; Totoson, P; Maguin-Gaté, K; Prigent-Tessier, A; Marie, C; Wendling, D; Moretto, J; Prati, C; Demougeot, C
Summary: To determine the effect of glucocorticoids (GCs) on endothelial dysfunction (ED) and on traditional cardiovascular (CV) risk factors in the adjuvant-induced arthritis (AIA) rat model. At the first signs of AIA, a high dose (HD) [10 mg/kg/day, intraperitoneally (i.p.), GC-HD] or low dose (LD) (1 mg/kg/day, i.p., GC-LD) of prednisolone was administered for 3 weeks. Endothelial function was studied in aortic rings relaxed with acetylcholine (Ach) with or without inhibitors of nitric oxide synthase (NOS), cyclooxygenase 2 (COX-2), arginase, endothelium derived hyperpolarizing factor (EDHF) and superoxide anions (O 2 – °) production. Aortic expression of endothelial NOS (eNOS), Ser1177-phospho-eNOS, COX-2, arginase-2, p22 phox and p47 phox was evaluated by Western blotting analysis. Arthritis scores, blood pressure, heart rate and blood levels of cytokines, triglycerides, cholesterol and glucose were measured. GC-HD but not GC-LD reduced arthritis score significantly and improved Ach-induced relaxation ( P  < 0·05). The positive effect of GC-HD resulted from increased NOS activity and EDHF production and decreased COX-2/arginase activities and O 2 – ° production. These functional effects relied upon increased phospho-eNOS expression and decreased COX-2, arginase-2 and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase expression. Despite the lack of effect of GC-LD on ED, it increased NOS and EDHF and down-regulated O 2 – ° pathways but did not change arginase and COX-2 pathways. GC-HD increased triglycerides levels and blood pressure significantly ( P  < 0·05). Both doses of GCs decreased to the same extent as plasma interleukin (IL)-1β and tumour necrosis factor (TNF)-α levels ( P  < 0·05). Our data demonstrated that subchronic treatment with prednisolone improved endothelial function in AIA via pleiotropic effects on endothelial pathways. These effects occurred independently of the deleterious cardiometabolic effects and the impact of prednisolone on systemic inflammation. Graphical Abstract: